The Role of Constitutionalism and Basic Structure in Exercising Political Power - Dr. Ashutosh Kundu (International Journal of Advanced Science and Technology, 2020)
A legal document of a country is an important legal norm in considering administration and future prospects of its citizens. The framers of the constitution of India tried hard to prepare a document which can fulfill various aspirations and demands of the society. It is a difficult job to anticipate future necessity of a country. In this respect, constitutionalism and basic structure plays a vital role to support the future demands. The constitution of India is an elaborative document in relation to various rights and duties .The dynamic aspect of the constitution of India is that the Constitution provided the responsibilities to the Supreme Court of India to interpret the provisions of the constitution where there is crisis in between ethos of the constitution and intention of the legislature. There are plethora of examples regarding responsible nature of judiciary in accessing dynamic political right to its citizens. Presently the citizen of India has got the right to use the option “NOTA” i.e., a voter has the right to caste his valuable vote if he or she finds no suitable candidates for his choice.Keywords: Constitutional sovereignty, penumbra, witch hunting, subjective satisfaction.